Development of billing post competency evaluation index system for nurses in China: a Delphi study - Jiao Liu; Huifang Qiu; Xiaohong Zhang; Cuiling Zhang; Fang He; Pan Yan (BMC, 2023)
Abstract Aim This study developed a set of competency evaluation indicators for billing nurses in China. Background In clinical practice, nurses often take up billing responsibilities that are accompanied by certain risks. However, the competency evaluation index system for billing nurses has not been established in China. Methods This study consisted of two main phases of research design: the first phase included a literature review and semi-structured interviews. Individual semi-structured interviews were conducted with 12 nurses in billing departments and 15 nurse managers in related departments. Concepts distilled from the literature review were linked to the results of the semi-structured interviews; this phase produced the first draft of indicators for assessing the professional competence of nurses in billing departments. In the second phase, two rounds of correspondence were conducted with 20 Chinese nursing experts using the Delphi method to test and evaluate the content of the index. The consensus was defined in advance as a mean score of 4.0 or above, with at least 75% agreement among participants. In this way, the final indicator framework was determined. Results Using the iceberg model as a theoretical foundation, the literature review identified four main dimensions and associated themes. The semi-structured interviews confirmed all of the themes from the literature review while generating new themes, both of which were incorporated into the first draft of the index. Then two rounds of the Delphi survey were conducted. The positive coefficients of experts in the two rounds were 100% and 95%, respectively, while the authority coefficients were 0.963 and 0.961, respectively. The coefficients of variation were 0.00-0.33 and 0.05-0.24, respectively. The competency evaluation index system for billing nurses consisted of 4 first-level indicators, 16 s-level indicators, and 53 third-level indicators. Conclusion The competency evaluation index system for billing nurses, which was developed on the basis of the iceberg model, was scientific and applicable. Implications for nursing management The competency assessment index system for billing nurses may provide an effective practical framework for nursing administration to evaluate, train, and assess the competency of billing nurses.